Management Strategy in Moving the Real Sector of Mosque-Based MSMEs - NASUTION, PROF. DR. M. YASIR; MM, IR PANDAPOTAN; M.E, ANGGI PRATIWI SITORUS; MM, KAMARUDDIN, . (The journal of contemporary issues in business and government, 2021)
Islam is a religion that brings grace to the whole of nature and a way of life in running economic activities based on the Quran and Sunnah. One of the ideal places to build people's financial lives toward prosperity and based on spiritual values is worship or mosque for Muslims. With a majority of Islamic people, Indonesia requires the establishment of mosques as centers of prayer and socio-economic activities for humanity. People's economic empowerment can be realised by managing mosque funds that are channelled directly to society and aimed at mobilising the real sector in small and medium enterprises. The whole sector's movement uses the mosque fund to include the management of ziswaf, the clerics', the Islamic institutions, and financial institutions that are the object of the study of Islamic economics. Management strategies are so much needed to realize this goal that they can generate useful and successful economic activities for the mashlahah, and that is the happiness and prosperity of the world and the afterlife.